Species Discrimination within the Metarhizium PARB Clade: Ribosomal Intergenic Spacer (rIGS)-Based Diagnostic PCR and Single Marker Taxonomy - Schuster, Christina (2023)
(1) Background: The entomopathogenic fungus Metarhizium anisopliae sensu lato forms a species complex, comprising a tight cluster made up of four species, namely M. anisopliae sensu stricto, M. pinghaense, M. robertsii and M. brunneum. Unambiguous species delineation within this “PARB clade” that enables both the taxonomic assignment of new isolates and the identification of potentially new species is highly solicited. (2) Methods: Species-discriminating primer pairs targeting the ribosomal intergenic spacer (rIGS) sequence were designed and a diagnostic PCR protocol established. A partial rIGS sequence, referred to as rIGS-ID800, was introduced as a molecular taxonomic marker for PARB species delineation. (3) Results: PARB species from a validation strain set not implied in primer design were clearly discriminated using the diagnostic PCR protocol developed. Using rIGS-ID800 as a single sequence taxonomic marker gave rise to a higher resolution and statistically better supported delineation of PARB clade species. (4) Conclusions: Reliable species discrimination within the Metarhizium PARB clade is possible through both sequencing-independent diagnostic PCR and sequencing-dependent single marker comparison, both based on the rIGS marker.